'Home' as an essentially contested concept and why this matters. Issue 4 (21st April 2023) - Meers, Jed
Abstract: This paper makes two interlinked arguments. First, that the 'concept of home' – the focus of a burgeoning literature within housing studies – meets Gallie's conditions for an 'essentially contested concept'. The influential theory, drawn on throughout the social sciences, seeks to explain concepts for which disputes are intractable; they cannot be settled by empirical evidence or argument. Second, that this 'essential contestability' is not just a theoretical label, it tells us something useful about how scholars can best employ the concept of home in their own work. The argument is put in three sections. The first provides a summary of Gallie's theory. The second argues that the concept of home meets Gallie's conditions for essential contestability. Finally, the third outlines the implications of the arguments put in the first two sections for scholars engaging with the concept of home.